Evolution of project based organization: A case study. Issue 8 (November 2015) - Kwak, Young Hoon; Sadatsafavi, Hessam; Walewski, John; Williams, Nigel L.
Abstract Little research has been conducted on how project-based organizations navigate internal and external pressures to develop and improve project competences over time. Using a cases study approach, this paper examines the development and implementation of project based organization over a period of 30 years. Overall, the evolution of project management competencies in the organization broadly followed the prevailing approaches in improving organizational management practices uncovered in review of literature. The organization's capability to adopt and implement project management frameworks improved over time as senior managers became more masterful at matching improvement actions into the organizational context. This research also presents how a systematic approach of project management maturity models for identifying and implementing project management practices and processes can increase the effectiveness and comprehensiveness of overall management practices. The study concludes with a series of recommendations in further improving project management practices and processes in project-based organizations.